SCIENCE TOPIC: WATER IS LIFE (Web of Teachers: Inderscience Research, 2024)
Water is a vital resource for all organisms on Earth. It plays a key role in many biological processes such as nutrition, respiration, thermoregulation and waste elimination. Without water, living organisms cannot exist, which is why it is often called liquid gold. Water is also an essential component for maintaining ecosystems and biodiversity on the planet. However, threats of pollution and water resource depletion threaten life on Earth, so it is important to take good care of this valuable resource.